2021
DOI: 10.1186/s12885-021-08713-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model of long-term advanced stage (IIIB-IV) EGFR mutated non-small cell lung cancer (NSCLC) survivors using real-life data

Abstract: Background There is a lack of useful diagnostic tools to identify EGFR mutated NSCLC patients with long-term survival. This study develops a prognostic model using real world data to assist clinicians to predict survival beyond 24 months. Methods EGFR mutated stage IIIB and IV NSCLC patients diagnosed between January 2009 and December 2017 included in the Spanish Lung Cancer Group (SLCG) thoracic tumor registry. Long-term survival was defined as be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…One was a large real-world cohort study from France that included 9,435 patients with non-squamous NSCLC [ 42 ]. The other included 505 patients from a Spanish registry [ 43 ]. Both studies reported exon 20 insertion prevalence within the range of values identified by this PLR, at 3.9% and 4.7% of all EGFR mutations, respectively [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One was a large real-world cohort study from France that included 9,435 patients with non-squamous NSCLC [ 42 ]. The other included 505 patients from a Spanish registry [ 43 ]. Both studies reported exon 20 insertion prevalence within the range of values identified by this PLR, at 3.9% and 4.7% of all EGFR mutations, respectively [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other included 505 patients from a Spanish registry [ 43 ]. Both studies reported exon 20 insertion prevalence within the range of values identified by this PLR, at 3.9% and 4.7% of all EGFR mutations, respectively [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutation plays a vital role in the pathogenesis of NSCLC, as it could lead to the metastasis of lung cancer tumors. 36 In this study, we found that CRNDE knockdown could inhibit the proliferation, migration, and invasion of EGFR-mutant NSCLC cells. Takahashi S et al found that CRNDE could promote the progression of EGFR-mutant NSCLC via regulation of eIF4A3/MUC1/ EGFR signaling.…”
Section: Discussionmentioning
confidence: 68%
“…Carcinoma de pulmão de células não pequenas (NSCLC) O tratamento e diagnóstico precoce podem melhorar o prognóstico, uma vez que a taxa de sobrevivência dos pacientes é de até 5 anos após o diagnóstico do câncer. Entretanto, a taxa de sobrevivência de um paciente com NSCLC dentro desses 5 anos, é de apenas 25% [4], sendo que os pacientes nos estágios IIIB (avançado) e IV (metastático), possuem taxa de sobrevida em torno de 12-24 meses, e um dos fatores que pode diminuir a sobrevida é ser adepto ao tabagismo [14].…”
Section: Resultsunclassified